Digital transformation in rural wine tourism: Lessons from Goriška Brda, Slovenia, for developing smart rural destinations in Serbia - Cvijanović, Drago; Vujko, Aleksandra; Cvijanović, Dušica (Hotel and Tourism Management, 2026)
Purpose – This study investigates the impact of digital innovation and sustainable practices on tourist behavior and destination attractiveness in rural wine regions, using Goriška Brda (Slovenia) as a case study. The goal is to identify key factors that influence visitation to smart rural wine destinations and explore how these practices can be adapted to enhance wine tourism in Serbia. Methodology – The research employed a quantitative approach, surveying 383 tourists in Brda municipality. Data were collected via a structured questionnaire using a five-point Likert scale. Factor analysis revealed three key constructs – VineTech Tourism, Smart Sustainability, and Digital Oenotravel – which were validated through Structural Equation Modeling (SEM) to test interrelationships and the theoretical model. A post-positivist epistemological approach guided the research design. Findings – The results confirmed that tourists value a blend of digital connectivity, sustainability, and immersive experiences. All three constructs significantly influenced tourist attitudes, supporting the hypothesis that smart rural tourism drives destination appeal and competitiveness. The 25–44 age group, particularly those with higher education, showed the strongest alignment with smart tourism values. Implications – Goriška Brda’s model offers a transferable blueprint for Serbian wine destinations, emphasizing community-based, tech-enabled, and sustainability-driven development to enhance rural tourism competitiveness and visitor engagement.